Dynamic Phasor Model of Grid-Connected Photovoltaic System in MATLAB/Simulink Considering Low Voltage Ride Through Characteristics for Voltage Stability Analysis of Power System - Dinh, Tien Luan; Nguyen, Hoang Viet; Hoang, Quoc Viet; Ngoc, Minh Truong (JST: Engineering And Technology For Sustainable Development, 2022)
This paper proposes a model of grid-connected photovoltaic (PV) system with low voltage ride through (LVRT) characteristic in MATLAB/Simulink based on dynamic phasor approach. Unlike all PV system models available in MATLAB/Simulink using detailed model with small capacity, the proposed model focuses on control loops of PV system to simulate a large capacity system that is appropriate for voltage stability analysis of power system installing high penetration level of PV generation. An intuitive and convenient tool for adjusting the LVRT characteristics of the PV system is also developed. The effectiveness of dynamic phasor model and the impact of the LVRT characteristic of the PV system on voltage stability are examined through MATLAB/Simulink simulations conducted on IEEE 9-bus test system. The simulation results provide an insight of how the system integrated with a large PV generation behaves under the disturbances. It also points out that the LVRT of the PV system is very important to the power system voltage stability.